Shoulder Manual Therapy for Aging and Older Adults–Part 2. Issue 3 (July 2015) - Chui, Kevin K.; Yen, Sheng-Che; Wormley, Michelle E.; Grimes, Jason
<x xml:space="preserve">Abstract</x> Adhesive capsulitis (AC) is a common cause of shoulder pain in aging and older adults. This narrative review synthesizes recent literature on manual therapy to the shoulder joint for AC. Emphasis has been placed on summarizing high-quality randomized clinical trials, systematic reviews with a narrative synthesis or meta-analysis, and clinical practice guidelines. The synthesis suggests that while there is limited high-quality evidence, manual therapy and exercise seem effective in improving outcomes in aging and older adults with AC, and there is limited evidence to support the superiority of manual therapy over other interventions. Additional research using consistent outcome measures is needed to establish the optimal manual therapy techniques and parameters for AC, both alone and in combination with exercise. Research that focuses exclusively on the effects of manual therapy on aging and older adults with AC is warranted.